IMPROVING TRAINING EFFICIENCY IN SCHOOL ATHLETICS SECTIONS (Web of Teachers: Inderscience Research, 2025)
Selection and orientation in sports are closely linked to the structure of improving an athlete's skills over many years. Based on this, it is advisable to highlight only five stages of selection to answer the question of whether athletes will be able to solve the tasks set before them at a certain stage of long-term training. Accordingly, it was noted that the main task of selection is defined at each stage.